Age-dependent trends in survival after adult in-hospital cardiac arrest. (June 2020) - Wiberg, Sebastian; Holmberg, Mathias J.; Donnino, Michael W.; Kjaergaard, Jesper; Hassager, Christian; Witten, Lise; Berg, Katherine M.; Moskowitz, Ari; Andersen, Lars W.; ,; Grossestreuer, Anne; Moskowitz, Ari; et al.
Abstract: Background: While survival after in-hospital cardiac arrest (IHCA) has improved in recent years, it remains unknown whether this trend primarily applies to younger IHCA victims. The aim of this study was to assess trends in survival to hospital discharge after adult IHCA across age groups from 2000 to 2016. Methods: This is an observational study of IHCA patients included in the Get With The Guidelines®-Resuscitation registry between 2000 and 2016. The primary outcome was survival to hospital discharge. Patients were stratified into five age groups: <50 years, 50–59 years, 60–69 years, 70–79 years, and ≥80 years. Generalized linear regression was used to obtain absolute survival rates over time. Results: A total of 234, 767 IHCA patients were included. The absolute increase in survival per calendar year was 0.8% (95% CI 0.7–1.0%, p < 0.001) for patients younger than 50 years, 0.6% (95% CI 0.4–0.7%, p < 0.001) for patients between 50 and 59 years, 0.5% (95% CI 0.4–0.6%, p < 0.001) for patients between 60 and 69 years, 0.5% (95% CI 0.4–0.6%, p < 0.001) for patients between 70 and 79 years, and 0.5% (95% CI 0.4–0.6%, p < 0.001) for patients older than 80 years. We observed a significant interaction between calendar year and age group ( p  < 0.001), indicating that the rate of improvement in survival over time was significantly different between age groups. Conclusions: For patients with IHCA, rates of survival to discharge have improved significantly from 2000 to 2016 across all age groups.